2021
DOI: 10.48550/arxiv.2111.04721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How binaries accrete: hydrodynamics simulations with passive tracer particles

Christopher Tiede,
Jonathan Zrake,
Andrew MacFadyen
et al.

Abstract: Linear analysis of gas flows around orbiting binaries suggests that a centrifugal barrier ought to clear a low-density cavity around the binary and inhibit mass transfer onto it. Modern hydrodynamics simulations have confirmed the low-density cavity, but show that any mass flowing from large scales into the circumbinary disk is eventually transferred onto the binary components. Even though many numerical studies confirm this picture, it is still not understood precisely how gas parcels overcome the centrifugal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…However, this does not affect the structure of the disc in a significant way. We investigated this by lowering the inner radius in locally isothermal test runs and found that 1 a bin offers accurate results while maintaining a reasonable timestep, in agreement with Tiede et al (2021) who showed that material within inside 1 a bin is accreted and does not change the dynamics of the outer disc.…”
Section: Disc Setupsupporting
confidence: 77%
See 2 more Smart Citations
“…However, this does not affect the structure of the disc in a significant way. We investigated this by lowering the inner radius in locally isothermal test runs and found that 1 a bin offers accurate results while maintaining a reasonable timestep, in agreement with Tiede et al (2021) who showed that material within inside 1 a bin is accreted and does not change the dynamics of the outer disc.…”
Section: Disc Setupsupporting
confidence: 77%
“…In this study we chose an inner domain boundary at 1 a bin such that the full interaction of the binary is not included for runtime reasons. Tiede et al (2021) shows that inside this radius nearly all mass is accreted and does not alter the dynamics of the outer disc. As Fig.…”
Section: Computational Domainmentioning
confidence: 92%
See 1 more Smart Citation
“…In the attempt to understand the final stages prior to merger of binary black holes (BBHs), numerical studies have addressed the problem of circumbinary accretion flows, taking the form of a disc, around a central BBH. Thanks to these studies, a global picture of the accretion structures under such circumstances has emerged, including a cavity and two streams feeding the individual BHs (MacFadyen & Milosavljević 2008, Shi et al 2012, Noble et al 2012, D'Orazio et al 2013, Gold et al 2014, Shi & Krolik 2015, Ragusa et al 2016, Armengol et al 2021, Tiede et al 2021, Liu 2021). In addition to those, the most surprising feature is certainly an overdensity, localized radially and azimuthally, which is found to orbit at the Keplerian period at the circumbinary disc inner edge, while being swept off by the spiral waves associated to the binary and therefore to the binary orbital period.…”
Section: Introductionmentioning
confidence: 99%
“…Near the circumbinary disc periapse, material can be captured by the binary or flung away from it through the cavity (e.g. Tiede et al 2021). Additionally, accretion discs ('minidiscs') form around each binary component.…”
Section: Introductionmentioning
confidence: 99%